Peranan Anggaran Proyek Dalam Meningkatkan Laba Kotor Studi kasus pada PT Sumber Sejahtera - Iriyadi, Iriyadi; Andrianto, Toni (STIE Kesatuan, 2007)
Competition cause all companies to be able to make business plans such as planning a budget if they want to make advancement in their business budget. Making a plan and controlling are absolutely needed so the budget may play a role well and the gross profit of the company will increase and the costs can be minimized.The budget role is very influenced by the process of composing it. The process of composing the budget at PT Sumber Sejahtera has some problems, such as: price, the kind of the raw material of material used, external factor (nature), and human resource. The purpose of the research is to find out the project budget composing process, the role of the project budget to increase the gross profit, and the system of cost control that is applied at PT Sumber Sejahtera.In order to be able to achieve the purpose of the research, the most appropriate procedure is needed to collect the data. In collecting the data, the author did some interviews and observations. The project budget composing at PT Sumber Sejahtera is based on field survey (technical and price survey), based on the previous budget of the similar previous project.In the implementation of the budget, there are some deviation of the planning of the budget cost. The deviation occurred in the use of material, the price of material, and daily cost of the labor.The result of the research show that the spare (unpredicted cost) on budget cost composing need to be evaluated. In the implementation of the project, keeping control over the performance of the field workers need to be improved. Therefore, the accuracy level of the budget cost planning can be presented better The Control system of the cost used is good enough.